BRAF V600E expression in ameloblastomas—A 36‐patient cohort from Helsinki University Hospital. (19th March 2019) - Kelppe, Jetta; Thorén, Hanna; Ristimäki, Ari; Haglund, Caj; Sorsa, Timo; Hagström, Jaana
Abstract: Objectives: We aimed to investigate BRAF V600E percentage immunohistochemically in ameloblastomas of a single institute cohort. We were interested if age, location, histological properties, or tumor recurrence depend on the BRAF status. Subjects, materials and methods: We had 36 formalin‐fixed, paraffin‐embedded ameloblastoma tissue samples of patients treated at the Helsinki University Hospital between the years 1983–2016. Tissue sections underwent immunohistochemistry by Ventana BenchMark XT immunostainer using Ms Anti‐Braf V600E (VE1) MAB. We used R 3.4.2 and RStudio 1.1.383 to conduct statistical analysis for BRAF positivity and earlier onset as well as tumor location. We used chi‐squared tests and 2‐by‐2 table functions to determine connections between BRAF positivity and recurrence, growth pattern, and type. Results: BRAF‐positive tumors occurred in younger patients compared to BRAF‐negative tumors ( p = 0.015) and they located mostly to the mandible ( p < 0.001). Growth patterns were limited to two in BRAF‐negative tumors when BRAF‐positive tumors presented with one to four growth patterns ( p = 0.02). None of the maxillary tumors showed BRAF positivity and of these, 72.2% recurred. Conclusions: An immunohistochemical BRAF marker could be a beneficial tool to predict the outcome of patients with this aggressive, easily recurring tumor.